Developing an Informed Curriculum for Initial Teacher Education (ITE): Building Student Teachersâ Theoretical and Practical Knowledge and Shaping Teacher Identity - Widodo, Ph.D., Handoyo Puji (Proceeding of International Conference on Teacher Training and Education, 2016)
Initial teacher education (ITE) programs play a pivotal role not only in helping student teachers build and enhance their theoretical knowledge and practical knowledge but also in assisting them to construct their teacher identity. At present, the ITE program also aims to prepare student teachers for the 21st century profession of teaching. Therefore, it is important to develop an informed curriculum for ITE, which caters to needs of student teachers and those of changing educational needs in tandem. In this plenary paper, I wish to flesh out such four key issues as a need for developing an informed ITE curriculum, domains of theoretical and practical knowledge student teachers need to learn, and role of teacher identity in the ITE program. I conclude by addressing a need for reframing an ITE curriculum in order to meet changing needs for educating and training more qualified teachers in the 21st century education and beyond.